2016
DOI: 10.1080/15476278.2016.1276146
|View full text |Cite
|
Sign up to set email alerts
|

Recellularization via the bile duct supports functional allogenic and xenogenic cell growth on a decellularized rat liver scaffold

Abstract: ABSTRACT. Recent years have seen a proliferation of methods leading to successful organ decellularization. In this experiment we examine the feasibility of a decellularized liver construct to support growth of functional multilineage cells. Bio-chamber systems were used to perfuse adult rat livers with 0.1% SDS for 24 hours yielding decellularized liver scaffolds. Initially, we recellularized liver scaffolds using a human tumor cell line (HepG2, introduced via the bile duct). Subsequent studies were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 34 publications
(57 reference statements)
2
30
0
Order By: Relevance
“…Studies investigating whether this approach is feasible are lacking. Several studies have successfully achieved reendothelialization (with or without coating the remaining ECM) and parenchymatous recellularization of liver scaffolds in vitro [8,20,64,73,112,113,[116][117][118][119][120][121][122][123]. Various cell types, such as hepatocytes (e.g.…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating whether this approach is feasible are lacking. Several studies have successfully achieved reendothelialization (with or without coating the remaining ECM) and parenchymatous recellularization of liver scaffolds in vitro [8,20,64,73,112,113,[116][117][118][119][120][121][122][123]. Various cell types, such as hepatocytes (e.g.…”
Section: Livermentioning
confidence: 99%
“…The existing studies have achieved an in vitro cultivation of the neo-livers for up to 28 days and revealed restored functionality (e.g. albumin secretion, urea production, ammonium metabolism and enzyme regulation), drug metabolism and viability of the seeded cells [8,20,64,73,79,81,112,113,[116][117][118][119]121]. According to Robertson et al, recellularized livers produce albumin and metabolize midazolam until the end of their study at 28 days.…”
Section: Livermentioning
confidence: 99%
“…Ko et al., utilized four vasculatures for the scaffold re‐endothelialization and such multi‐route approach might also facilitate the parenchymal repopulation efficiency. In addition to the vasculature, bile ducts were also utilized for parenchymal recellularization and showed encouraging results . Novel approaches that would increase the recellularization uniformity are of high interests.…”
Section: Liver Scaffold Recellularizationmentioning
confidence: 99%
“…In addition to the vasculature, bile ducts were also utilized for parenchymal recellularization and showed encouraging results. 90 Novel approaches that would increase the recellularization uniformity are of high interests.…”
Section: Recellularization With Hepatocyte and Nonparenchymal Cellsmentioning
confidence: 99%
“…Recent studies using in vitro 3D hepatocyte culture include systems based on microcarriers [3], hollow fibers [4][5][6], decellularized liver scaffolds [7][8][9], spheroidal aggregates [10][11][12][13], cell sheets [14][15][16], microfluidic chips [17][18][19][20], and 3D bioprinted cultures [21][22][23][24]. Despite the advantages of increased hepatocyte viability compared to 2D cultures, such systems share a common shortcoming.…”
Section: Introductionmentioning
confidence: 99%